The international bank lending channel of unconventional monetary policy - Johannes Gräb; Dawid Żochowski (European Central Bank (ECB), 2017)
We use a confidential euro area bank-level data set of close to 250 banks to assess outward and inward spillovers of unconventional monetary policies on bank lending. We find that euro area banks increase lending to the rest of the world in response to non-standard ECB monetary policy accommodation. We also find strong evidence that euro area banks increase lending to the domestic non-financial private sector in response to accommodative unconventional monetary policy measures in the US. Inward and outward spillovers are substantially stronger for euro area banks which are liquidity constrained and which rely more on internal capital markets. This suggests that bank-specific supply effects, stemming from banks' increased ability to lend following a central bank balance sheet expansion, are a major driver of mon- etary policy spillovers, providing strong support to the existence of an international bank lending channel that prevails at the effective lower bound.
Keywords: E44; E52; G01; 330; international bank lending channel; monetary policy; quantitative easing; cross-border spillovers